Prof. Kosta Pergelov's Understanding of Fair Value and Efficiency and Their Contemporary Presentation - Kavaldzhieva, Kalina (Research Papers, 2023)
The development of accounting theory is extremely important, as can be seen from the point of view of the theory itself and for practice. The accounting interpretation of capital has an extremely important role, including issues of efficiency and analysis. The current concept of efficiency and its manifestation through fair value dates back to ancient times. The need for this concept is dictated primarily by the economy, production and business processes, as well as the creation of qualitatively new prerequisites for creating new value. This also means preparing for building new, institutional and organizational relationships in society. {~~They are~>These are~~} key to governance.
Keywords: Capital; Accounting; Еfficiency; Fairness